A person-centered, latent profile analysis of psychological capital. Issue 1 (February 2019) - Bouckenooghe, Dave; De Clercq, Dirk; Raja, Usman
This inquiry seeks to clarify whether and how various combinations of the four core components of psychological capital (PsyCap)—self-efficacy, hope, optimism, and resilience—differentially affect workplace outcomes. To gain such in-depth understanding, this study undertakes a person-centered, latent profile analysis of PsyCap. Several distinct PsyCap component profiles emerge and remain consistent across two studies; these profiles in turn exert significantly different effects on work engagement and job performance. Compared with a more commonly used variable-centered approach, this person-centered approach represents a valuable complement that can expand the understanding and implications of PsyCap. JEL classification:M10, M19